PBL-Based Google Sites Enhance Social Studies Understanding among PGSD Students: An Experimental Study - Nuranjani; Supartinah; Dwi Wijayanti (Universitas Pendidikan Ganesha, 2023)
Understanding the concept is a competence that prospective elementary school teachers must possess. However, the understanding of the social studies concept of PGSD students is still relatively low. Therefore, an innovation is needed to solve this problem. This study aims to analyze whether the application of PBL-based Google Sites can enhance student’ understanding of social studies concepts. The research method used was Quasi-Experimental with a Non-equivalent control group pretest-posttest design. The study subjects used two groups selected as the experimental group and the control group. Data collection techniques are used in the form of tests and observations. As for data analysis using normality test, homogeneity test and independent samples t-test. To see an increase in students' understanding of social studies concepts after conducting experiments with the N-Gain test. The results of the independent samples test showed that the use of PBL-based Google Sites was more effective than learning that did not use PBL-based Google Sites with a difference in the N-Gain calculation results of 15.29% in increasing understanding of social science concepts for PGSD students. It was concluded that the implementation of PBL-based Google Sites could improve students' understanding of social studies concepts.